Were human babies used as bait in crocodile hunts in colonial Sri Lanka? - Anslem de Silva; Ruchira Somaweera (Journal of Threatened Taxa, 2015)
Use of live animals as bait is not an uncommon practice in hunting worldwide.  However, some curious accounts of the use of human babies as bait to lure crocodiles in sport hunting exist on the island of Sri Lanka, where sport hunting was common during the British colonial period.  Herein we compile the available records, review other records of the practice, and discuss the likelihood of the exercise actually having taken place.